New interaction tools for preserving an old language - Plimmer, Beryl; Liang, He; Tariq, Zaman; Kasun, Karunanayaka; Yeo, Alvin Wee; Jengan, Garen; Blagojevic, Rachel; Do, Ellen Yi-Luen (Association for Computing Machinery, 2015)
The Penan people of Malaysian Borneo were traditionally nomads of the rainforest. They would leave messages in the jungle for each other by shaping natural objects into language tokens and arranging these symbols in specific ways – much like words in a sentence. With settlement, the language is being lost as it is not being used by the younger generation. We report here, a tangible system designed to help the Penans preserve their unique object writing language. The key features of the system are that: the tangibles are made of real objects; it works in the wild; and new tangibles can be fabricated and added to the system by the users. Our evaluations show that the system is engaging and encourages intergenerational knowledge transfer, thus has the potential to help preserve this language.